Pemanfaatan Teknik Kultur In Vitro untuk Konservasi Plasma Nutfah Ubi-ubian - Nurwita Dewi; Iswari S. Dewi; Ika Roostika (Jurnal AgroBiogen, 2014)
Except for potato, sweet potato, taro, yam, andcassava, most of tuber crops are considered as underutilizedcrops. However, tuber crops are potential as alternativecarbohydrate sources, so they can be used as food reservesto face global climate change that affects food security incertain area throughout the world, including Indonesia.Having high diversity in tuber crops germplasm, Indonesiamust be able to conserve those germplasm to ensure theiravailability in the future. In the future, without ignoring allthe probable constraints, the prospect in utilization of in vitroculture technique will be higher for improvement ofconservation and management of genetic resources in theform of active and base collections. In this paper, strategy indeveloping in vitro collection of tuber crops germplasm, i.e.slow growth technique for medium term storage andcryopreservation technique for long term storage, isdiscussed including how to analyze genetic stability of thecollections. Several national and international researchcenters dealing with research and development of in vitroconservation technique are presented.